Internet connectivity disruption in Malaysia (Malaysia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Malaysia. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: MY-2026-0044. Severity: critical. Confidence: 75%